1995
DOI: 10.1182/blood.v86.8.3083.bloodjournal8683083
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to phosphatidylethanolamine (PE) recognize a kininogen- PE complex

Abstract: Demonstration of autoimmune antiphospholipid antibodies (aPA) to negatively charged phospholipids (PL) in an enzyme-linked immunosorbent assay (ELISA) requires the presence of certain phospholipid-binding plasma proteins, eg, beta 2-glycoprotein I. We found a requirement for plasma against the electrically neutral or zwitterionic phospholipid, phosphatidylethanolamine (PE). Two of these PE-binding plasma proteins were identified as high molecular weight kininogen (HMWK) and low molecular weight kininogen (LMWK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(55 citation statements)
references
References 1 publication
2
52
1
Order By: Relevance
“…Sera from RPL women positive for aPE and/or aFXII antibodies or without any antibodies were used in the study. IgG was purified from sera by diethylaminoethyl (DEAE)–Sepharose followed by protein G‐Sepharose described elsewhere 13 . IgG fraction was used for the study, because our previous reports revealed that the IgG fraction is most persistent and pathogenic in patients with reproductive failure 3,4,37 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sera from RPL women positive for aPE and/or aFXII antibodies or without any antibodies were used in the study. IgG was purified from sera by diethylaminoethyl (DEAE)–Sepharose followed by protein G‐Sepharose described elsewhere 13 . IgG fraction was used for the study, because our previous reports revealed that the IgG fraction is most persistent and pathogenic in patients with reproductive failure 3,4,37 …”
Section: Methodsmentioning
confidence: 99%
“…Sera from both patient A and patient B showed negative for all other aPA. All the aPA were measured as described elsewhere 13–15,19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG was purified from sera by diethyl aminoethyl (DEAE)‐Sepharose followed by protein G‐Sepharose as described elsewhere . IgG fraction was used for the study, because our previous reports revealed that the IgG fraction is most frequent and pathogenic in patients with reproductive failure …”
Section: Methodsmentioning
confidence: 99%
“…Because PE is a major component of both the outer and inner leaflet of cell plasma membranes, production of aPE may interfere with normal cell functions. Sugi and McIntyre reported that certain aPE are not specific for PE per se, but are directed to PE‐binding plasma proteins, kininogens 10 . Kininogens are known as members of kallikrein–kinin system.…”
Section: Introductionmentioning
confidence: 99%